IDENTIFIKASI FAKTOR-FAKTOR PENYEBAB KECELAKAAN LALU LINTAS JALAN RAYA BUKITTINGGI-MEDAN KM 8 AGAM - Vira Putri Elva Riska; Helga Yermadona; Yorizal Putra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
On the Bukittinggi-Medan km 8 highway, which is located in Palupuah District, we can find many lack of road facilities so that accidents often occur. human life, with these conditions, efforts are needed to determine the factors and characteristics that cause the occurrence of direct accidents and handling efforts to reduce accidents. The first step is to search for primary data in order to find out the cause of the accident. Secondary data was obtained from the Agam District Police data, namely the data on the number of accidents in 2017-2021. From the results of the analysis of the factors causing the accident, the Human Factor is in the highest category with a percentage of 55.55% and the highest accident rate will occur in 2021, which is as many as 7 accident cases. And the results of the correlation showed that the causes of accidents were human factors very highly correlated (r) 0.942, vehicle factors were strongly correlated (r) 0.843, road factors had a low but definite correlation (r) 0361, environmental factors were strongly correlated (r) -0.906. Suggestions from this study are handling and human awareness as drivers to increase awareness and obey in traffic. Keywords : accident factor, correlation, traffic accident.